Pengaruh Pembiayaan UED-SP Terhadap Efektivitas Usaha Masyarakat Desa Pada Bidang Pertanian Kecamatan Bantan - Irawan Fakhrudin Mahalizikri; Nelly Agus Tantiana (JAS (Jurnal Akuntansi Syariah), 2020)
This research aims to determine how much influence the funding of UED-SP on the efforts of rural communities in agriculture in the District of Bantan. The type of data from this research is quantitative using primary and secondary data. The population in this research were all customers who borrowed UED-SP in agriculture in the District of Bantan, amounting to 261 people, while the sample taken was as many as 158 people. The data analysis technique used is simple linear regression. The results of this research are that there is a significant influence between the funding of UED-SP on the effectiveness of rural communities in the agriculture sector of Bantan District, with a percentage value of 54.4%.